Burnout Among Forensic Psychologists: An Examination of the Relationship Between Stress, Selfcare, and Help Seeking - Kenosi, Lorato Itumeleng; Draper, David; Roddy, Allison; Domingo, Aldwin (Advances in Social Sciences Research Journal, 2026)
Due to the nature of their work, mental health professionals are prone to stress that can escalate into burnout with detrimental personal and professional effects. Selfcare is effective in managing stress and preventing burnout, but burnout is better managed by help-seeking behavior that is determined by attitudes and intentions and influenced by demographic and occupational factors. Therefore, stress, selfcare, help-seeking attitudes, help-seeking intentions as well as demographic and occupational factors are predictors of burnout among mental health professionals, including psychologists. However, due to the scarcity of research, burnout predictors among forensic psychologists are often deduced from related professions, but forensic psychologists need to be studied as a distinct professional population owing to their unique working conditions, clients, and ethical requirements. Therefore, this quantitative study employed a quasi-experimental design to examine burnout predictors among forensic psychologists in the United States and used multiple regression to test the study hypotheses. Overall, 85 forensic psychologists participated in this study. The study results indicated a significant mixed correlation between stress, selfcare, help-seeking attitudes, help-seeking intentions, age, and length of practice and three burnout components (emotional exhaustion, depersonalization, and personal accomplishment). This study filled gaps in the literature relating to burnout among forensic psychologists in the United States, may incite further research on the topic, and will assist relevant stakeholders in making informed decisions relating to preventing and managing burnout among this professional population.